An Effective Method to Construct Cluster‐based Frameworks with Multifarious Structures, Luminescence, and Sorption Properties. Issue 2 (30th November 2016) - Li, Qipeng; Yu, Panpan; Luo, Jiagang; Qi, Cen; Zhang, Zejun; Qian, Jinjie
Abstract : An effective method was developed for the synthesis of three cluster‐based frameworks with multifarious secondary building units (SBUs) and various structures, which were formulated as [Me2 NH2 ]2 [Zn10 (BTC)6 (μ3 ‐O)(μ4 ‐O)(H2 O)5 ]· 3DMA· 9H2 O (FJI ‐3 ), [Me2 NH2 ]2 [Zn9 (μ3 ‐OH)2 (BTC)6 (H2 O)3 ]· 5DMA· 6H2 O (FJI ‐4 ) and [Me2 NH2 ][Zn3 (μ3 ‐OH)(BTC)2 DMF]· H2 O (FJI ‐5 ) (H3 BTC = 1, 3, 5‐benzenetricarboxylic acid, DMA = N, N ′‐dimethyl acetamide and DMF = N, N ′‐dimethyl formamide), respectively. X‐ray structural analysis reveals thatFJI ‐3 displays 3D highly porous metal‐organic framework with four kinds of microporous cages constructed by two paddle‐wheel Zn2 (CO2 )4, trimeric Zn3 O(CO2 )6, and tetrameric Zn4 O(CO2 )6 SBUs.FJI ‐4 exhibits 3D microporous MOFs with a dodecahedral cavities built by paddle‐wheel Zn2 (CO2 )4 and trimeric Zn3 O(CO2 )6 .FJI ‐5 shows 3D microporous MOFs with an 1D channel assembled by the Zn3 O(CO2 )6 SBUs. In addition, the fluorescence and sorption properties in these cluster‐based frameworks were also investigated. Furthermore, the method employed in this work may provide an useful approach to the design and synthesis of novel cluster‐based frameworks. Abstract :